2022
DOI: 10.3390/ijms232012160
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High CO2 and Strigolactones on Shoot Branching and Aphid–Plant Compatibility Control in Pea

Abstract: Elevated atmospheric CO2 concentrations (eCO2) regulate plant architecture and susceptibility to insects. We explored the mechanisms underpinning these responses in wild type (WT) peas and mutants defective in either strigolactone (SL) synthesis or signaling. All genotypes had increased shoot height and branching, dry weights and carbohydrate levels under eCO2, demonstrating that SLs are not required for shoot acclimation to eCO2. Since shoot levels of jasmonic acid (JA) and salicylic acid (SA) tended to be lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Christine H. Foyer and co-workers showed that the phytohormones strigolactone (SL) and gibberellin are involved in host susceptibility in pea-A. pisum interaction, but the aphid-plant compatibility control of these phytohormones is not changed by eCO 2 [8].…”
Section: Aphid-plant Interactionsmentioning
confidence: 99%
“…Christine H. Foyer and co-workers showed that the phytohormones strigolactone (SL) and gibberellin are involved in host susceptibility in pea-A. pisum interaction, but the aphid-plant compatibility control of these phytohormones is not changed by eCO 2 [8].…”
Section: Aphid-plant Interactionsmentioning
confidence: 99%